2016
DOI: 10.1016/j.engstruct.2016.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear fibre element modelling of RC bridge piers considering inelastic buckling of reinforcement

Abstract: An advanced modelling technique is developed to model the nonlinear cyclic response of circular RC columns using fibre-based section discretisation method. A comparison between different reinforcing steel models is made. Through a comprehensive parametric study the influence of inelastic buckling of vertical reinforcement on the cyclic response of circular RC columns is investigated. The results have been compared and validated against a set of experimental datasets. The proposed calibrated model accounts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 35 publications
1
66
0
Order By: Relevance
“…The failure mode in column 1015 starts with buckling (not as severe as columns 415 and 815) but is followed by fracture of bars in tension without any severe core concrete crushing. This behaviour was observed in the experimental testing by Lehman and Moehle (2000) and numerical modelling by Kashani et al (2016) and also reported by other researchers Eberhard 2003, 2006). Similar differences are appreciated in the nonlinear dynamic response of column 1015 in the IDA graphs.…”
Section: Definition Of Ultimate Limit State Drift Of Proposed Columnssupporting
confidence: 50%
See 3 more Smart Citations
“…The failure mode in column 1015 starts with buckling (not as severe as columns 415 and 815) but is followed by fracture of bars in tension without any severe core concrete crushing. This behaviour was observed in the experimental testing by Lehman and Moehle (2000) and numerical modelling by Kashani et al (2016) and also reported by other researchers Eberhard 2003, 2006). Similar differences are appreciated in the nonlinear dynamic response of column 1015 in the IDA graphs.…”
Section: Definition Of Ultimate Limit State Drift Of Proposed Columnssupporting
confidence: 50%
“…Therefore, this combined model accounts for the influence of inelastic buckling and low-cycle fatigue degradation. Through a comprehensive parametric study the 'optimum' pinching parameters of the model under cyclic loading are obtained (Kashani et al 2016). A more detailed discussion of the model development and calibration can be found elsewhere , Kashani et al 2016).…”
Section: Uniaxial Materials Models For Reinforcing Steelmentioning
confidence: 99%
See 2 more Smart Citations
“…() This may result in a reduction of section moment capacity, thereby adversely affecting the section/member ductility. () In cyclically loaded RC members, when unloading from tension, concrete does not carry compressive stress until the cracks are completely closed, but the longitudinal bars develop large compressive stress well before the cracks close (ie, when the strain is still tensile). Hence, during most inelastic cyclic response, cracked concrete does not contribute much to the section equilibrium, and the tensile force carried by bars and the applied axial compression force are balanced only by the compressive forces carried by bars in the compression side.…”
Section: Introductionmentioning
confidence: 99%